Intellectual property provisions in regional trade agreements: Revision and update - Raymundo Valdés; Maegan McCann (World Trade Organization (WTO), 2014)
This is a revision and update of "Intellectual Property Provisions in Regional Trade Agreements" by Valdés and Runyowa (2012). This paper adjusts the methodology applied to assess the intellectual property (IP) provisions contained in regional trade agreements (RTAs) and the aggregation of such provisions into groups; it also updates the RTAs surveyed, from 194 in November 2010 to 245 in February 2014. New information contained in this revision relates to three IP-related investment and non-violation provisions in RTAs. The methodological revisions and new information result in changes to the assessment of the IP content of certain RTAs while the update reveals a growing and increasingly complex network of RTAs with IP content. This revision also provides new insights into possible improvements to the methodological toolkit for analysing IP in RTAs. The paper assembles detailed information about the IP provisions contained in active RTAs notified to the WTO. The goal was to expand beyond the more commonly studied RTAs, to review the full array of agreements notified to the WTO and thus to enable consideration of the implications of this diverse range of norm-setting activity for the multilateral system. Mapping of the IP content in RTAs involving parties from all regions and levels of development is necessary to better understand cross-cutting trends in RTAs, and how all the parts of the international IP framework influence each other. [...]
Keywords: F13; F15; F53; O34; 330; Regional Trade Agreements; Intellectual Property Rights; WTO; TRIPS